2016
DOI: 10.1186/s40337-016-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of participants’ reflections on body image during participation in a randomized controlled trial of acceptance and commitment therapy

Abstract: BackgroundNegative body image is a risk factor for development and relapse in eating disorders (ED). Many patients continue to be dissatisfied with their body shape or weight after treatment. This study presents a qualitative analysis of written reflections on body image from patients with an ED and a negative body image before and after an Acceptance and Commitment Therapy group treatment at a specialized ED-unit.MethodBefore and after the treatment participants (n = 47) answered a questionnaire with open end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Hence, there is little opportunity to compare these findings with those of similar pilots/evaluations. Nonetheless, the current findings are comparable to research findings on ACT applied to other clinical areas, such as chronic pain (Barker and McCracken, 2014), eating disorders (Fogelkvist et al, 2016), symptoms of psychosis (Bacon et al, 2014) and schizophrenia (Asher and Gask, 2010). For example, the theme pertaining to "increased awareness of personal values" is similar to that found in research by Barker and McCracken (2014).…”
Section: Discussionsupporting
confidence: 83%
“…Hence, there is little opportunity to compare these findings with those of similar pilots/evaluations. Nonetheless, the current findings are comparable to research findings on ACT applied to other clinical areas, such as chronic pain (Barker and McCracken, 2014), eating disorders (Fogelkvist et al, 2016), symptoms of psychosis (Bacon et al, 2014) and schizophrenia (Asher and Gask, 2010). For example, the theme pertaining to "increased awareness of personal values" is similar to that found in research by Barker and McCracken (2014).…”
Section: Discussionsupporting
confidence: 83%
“…Since, usually medically ill patients express more negative feelings toward their bodies than healthy persons, patients tend to focus on dissatisfaction of the body part or the function affected by the illness and finally cause experiential avoidance. In this regard, studies that have worked on body consciousness and awareness have found that by decreasing the experiential avoidance, psychological flexibility will improve ( 35 , 42 ). For instance, the effect of mindfulness exercises on body awareness in women with sexual dysfunction were reflective of the considerable contribution of mindfulness exercises to the improvement in the symptoms of sexual dysfunction and the body-image problem ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than listening to evaluative thoughts that suggest continued avoidance of situations that provoke inner painful experiences, they were prompted to do the opposite if it is in line with what they value. A more detailed description of the intervention has been published previously [ 13 ].…”
Section: Methodsmentioning
confidence: 99%